Electrical Impedance Spectrometry - Application to PET (Polyethylene Terephthalate) relative humidity detection and preliminary studies towards peloids characterization - Duarte, Emanuel Costa (2018)
Dissertação de Mestrado Integrado em Engenharia Física apresentada à Faculdade de Ciências e Tecnologia